2011
DOI: 10.1136/pgmj.2011.118398
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory distress syndrome and acute lung injury

Abstract: Acute respiratory distress syndrome (ARDS) is a life threatening respiratory failure due to lung injury from a variety of precipitants. Pathologically ARDS is characterised by diffuse alveolar damage, alveolar capillary leakage, and protein rich pulmonary oedema leading to the clinical manifestation of poor lung compliance, severe hypoxaemia, and bilateral infiltrates on chest radiograph. Several aetiological factors associated with the development of ARDS are identified with sepsis, pneumonia, and trauma with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
192
0
11

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(204 citation statements)
references
References 110 publications
1
192
0
11
Order By: Relevance
“…1,2 There are many etiological factors contributing to ARDS. However, only a few account for majority of the cases like sepsis from both pulmonary and non-pulmonary origin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 There are many etiological factors contributing to ARDS. However, only a few account for majority of the cases like sepsis from both pulmonary and non-pulmonary origin.…”
Section: Introductionmentioning
confidence: 99%
“…6 The diagnosis of ARDS is done based on three main criteria's: the presence of acute severe hypoxemia, bilateral infiltrates on chest radiography (CXR), and absence of raised pulmonary artery wedge pressure. 1 The pathophysiology of ARDS, the most important feature is increased capillary permeability. This is due to damage of the capillary endothelium and alveolar epithelium lining causing accumulation of protein rich fluid inside the alveoli.…”
Section: Introductionmentioning
confidence: 99%
“…Acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) are life-threatening diseases that present with progressive dyspnea, refractory hypoxemia and a marked increase in difficulties breathing (1,2). Since the initial description of ARDS in 1967 (3), there have been advances in the pathogenesis and treatment of this disease, however, challenges remain.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological investigations suggest that ARDS remains a significant health burden with substantial morbidity and mortality (4). The majority of patients require endotracheal intubation and positive pressure ventilation (1,2) and account for millions of days spent in intensive care units (5). In recent years, treatments of ALI/ARDS with improved efficacy have been sought, and studies have indicated that liquid ventilation with perfluorocarbon (PFC) compounds is a promising therapeutic approach (6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Acute lung injury (ALI), characterized by unbalanced inflammatory responses, is a leading cause of acute respiratory failure and multiple organ dysfunctions (Dushianthan et al, 2011). In experimental models, ALI can be triggered by either infectious or noninfectious stimuli, such as lipopolysaccharide (LPS) (Favarin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%